Through the Iron Curtain: the Taizé ecumenical experience in Eastern Europe (1960–1989) - Scatena, Silvia; Sagert, Dietrich; Alois Frère (Fscire research and papers, 2023)
The history of the intertwined relationships woven by the Taizé Community amongst Christians of Eastern European countries in the second half of the last century has not yet been written. Yet it is a fundamental chapter for understanding the unique international influence of the community. The encounter with the different faces of a Christian youth beyond the Iron Curtain, who in Taizé had their first experience of a unified European space, was to become one of the main directions of the community's effort from the early 1960s. The contributions of this volume intend to throw a first light on this story, relying on a completely unpublished documentation and on the testimony of many protagonists involved in the construction of this unique continental and ecumenical network